Experimental and numerical investigations of full-field strain measurement and fracture parameter of lead-free solder using DIC technique - Bang, Tao Quang; An, Nguyen Van Thien; Benabou, Lahouari; Hung, Nguyen Xuan (Vietnam Journal of Mechanics, 2020)
In this study, rupture of notched SENT specimens fabricated from a novel lead-free solder alloy is investigated. The lead-free solder alloy, focused on in this study, is particularly used as interconnect material in power modules of electric vehicles. Its commercial denomination is InnoLot and it can be used in harsh environments thanks to its improved reliability. Up to now, studies on their resistance to rupture remain relatively limited. Yet the comprehension of fracture behavior is essential for the correct design of the electronic packages which must be robust against fatigue and vibrations loads. The tests are performed with the help of a micro-tensile testing machine equipped with an optical system for full-field measurements with Digital Image Correlation. The images are taken at successive steps of deformation and the displacement field is measured in a region of interest which is the singularity dominated zone surrounding the plastic zone at the crack tip. The procedure consists then in comparing the measured field with the theoretical field given by the Williams’ solution. The stress intensity factor is calculated by fitting the analytical fields to the experimental data. The effects of the size and shape of the zone of data collection, as well as that of the number of terms considered in the Williams’s expansion series, are examined in the study. A method is also proposed for the automatic crack tip detection. From these finding, it is easy to predict the crack propagation and failure mechanism of solder joint. In addition, the theoretical solution of displacement, given by the Williams series, is compared with measurements to identify the coefficients of these series, including the stress intensity factor. Finally, a 5-order truncation of the Williams series seems sufficient to obtain a correct estimate of the stress intensity factor.